The Reign of Neoliberalism and the Reign of God: Ignacio Ellacuría’s Anthropology as a Critique of Neoliberalism - Orozco, Amirah A. (Theological studies, 2026)
This article uses the work of Ignacio Ellacuría to articulate a concept of sin in light of the literature on how neoliberalism shapes us into homo oeconomicus. Ellacuría describes sin as the stifling of the theologal dimension of historical reality; it rejects the fundamental affirmation that all things ?have been formed according to the triune life and refer essentially to that life.? Under neoliberalism, such a concept of sin is hollowed out, as transgressions are always and only against the market: The always elusive economic market is the only victim of history. The article ends with how the denunciation of sin has functioned as a critique of market logics on the southern US border.